Uses and Appropriation of Technologies in Initial Teacher Training Centers: A Comparative Study in Uruguay and Chile - Questa-Torterolo, Mariela (2024)
Objective. This article aims to compare the use and appropriation of digital technologies (ICT) by faculty in initial teacher training centers in Uruguay and Chile. Methodology. This research employed a mixed, sequential exploratory, quantitative-qualitative approach and data analysis, including two stages: (I) an online questionnaire administered to directors of centers in Uruguay and Chile; (II) interviews and discussion groups with members of selected centers in each country. Results. Results show that Chilean teachers most frequently use laptops, followed by cell phones. In Uruguay, the order is reversed. Concerning the use of ICT for pedagogical or professional development purposes, including videoconferencing, the creation of professional learning communities, and content creation, Chile is better positioned. Nonetheless, because of the pandemic and the adoption of other techniques, Uruguay has begun to increase its use of ICT for pedagogical purposes. Likewise, teachers have been identified both as facilitators of digital inclusion, thanks to their motivation, and as obstacles, due to fears, advanced age, and training. Conclusions. These findings show the relevance to keep intervening at the level of teacher education as a key focus to improve digital inclusion for pedagogical and professional development purposes.